Cover Feature: True Blue Through Oxidation—A Thiaazulenic Heterophenoquinone as Electrochrome (Chem. Eur. J. 21/2019). Issue 21 (19th March 2019) - Intorp, Sebastian N.; Kushida, Soh; Dmitrieva, Evgenia; Popov, Alexey A.; Rominger, Frank; Freudenberg, Jan; Hinkel, Felix; Bunz, Uwe H. F.
Abstract : A new blue chromophore for electrochromic devices : Electrochromism is an intriguing feature that describes the reversible switching between two or more colored states upon oxidation or reduction. Especially the switching from colored to colorless states is an attractive property for application in windows and glasses. In this work, a new intensely blue thiaazulenic quinone (TAQ) and its switching to a colorless anionic state is described. This study sheds light on the electronic processes upon electron injection. Prototypes of electrochromic devices show a high coloration efficiency and complete reversibility after multiple switching cycles. More information can be found in the Communication by U. H. F. Bunz et al. on page 5412 .